Ferngully: the last rainforest ; Ferngully 2, the magical rescue [videorecording (DVD)]. - Cox, Jim, (Screenwriter); Tulloch, Richard, (Screenwriter); Young, Diana (Children's author) (Shout! Factory Kids, 2023)
"FernGully: the last rainforest": The magical inhabitants of a rainforest fight to save their home, which is threatened by logging and a polluting force of destruction called Hexxus.